Quliyat e iqbal - Allama iqbal (Nawab sons publication;891 Lahore, 2012)
"Quliyat-e-Iqbal" is a comprehensive collection of the works of Allama Muhammad Iqbal, showcasing his profound philosophical thoughts, poetic brilliance, and visionary ideas on spirituality, self-empowerment, and the future of the Muslim world.